Model of complex rehabilitation for patients with a simple form of schizophrenia - V. V. Chuhunov; V. O. Kurylo; V. L. Pidlubnyi; S. M. Kanyhina (Zaporožskij Medicinskij Žurnal)
Model of complex rehabilitation for patients with a simple form of schizophrenia